High-efficiency editing in hematopoietic stem cells and the HUDEP-2 cell line based on in vitro mRNA synthesis - Papaioannou, Nikoletta Y.; Patsali, Petros; Naiisseh, Basma; Papasavva, Panayiota L.; Koniali, Lola; Kurita, Ryo; Nakamura, Yukio; Christou, Soteroula; Sitarou, Maria; Mussolino, Claudio; Cathomen, Toni; Kleanthous, Marina; et al. (Frontiers in Genome Editing, 2023)
Genome editing tools, such as CRISPR/Cas, TALE nucleases and, more recently, double-strand-break-independent editors, have been successfully used for gene therapy and reverse genetics. Among various challenges in the field, tolerable and efficient delivery of editors to target cells and sites, as well as independence from commercially available tools for flexibility and fast adoption of new editing technology are the most pressing. For many hematopoietic research applications, primary CD34+ cells and the human umbilical cord-derived progenitor erythroid 2 (HUDEP-2) cell line are highly informative substrates and readily accessible for in vitro manipulation. Moreover, ex vivo editing of CD34+ cells has immediate therapeutic relevance. Both cell types are sensitive to standard transfection procedures and reagents, such as lipofection with plasmid DNA, calling for more suitable methodology in order to achieve high efficiency and tolerability of editing with editors of choice. These challenges can be addressed by RNA delivery, either as a mixture of guide RNA and mRNA for CRISRP/Cas-based systems or as a mixture of mRNAs for TALENs. Compared to ribonucleoproteins or proteins, RNA as vector creates flexibility by removing dependence on commercial availability or laborious in-house preparations of novel editor proteins. Compared to DNA, RNA is less toxic and by obviating nuclear transcription and export of mRNA offers faster kinetics and higher editing efficiencies. Here, we detail an in vitro transcription protocol based on plasmid DNA templates with the addition of Anti-Reverse Cap Analog (ARCA) using T7 RNA polymerase, and poly(A) tailing using poly(A) polymerase, combined with nucleofection of HUDEP-2 and patient-derived CD34+ cells. Our protocol for RNA-based delivery employs widely available reagents and equipment and can easily be adopted for universal in vitro delivery of genome editing tools. Drawing on a common use case, we employ the protocol to target a β-globin mutation and to reactivate γ-globin expression as two potential therapies for β-hemoglobinopathies, followed by erythroid differentiation and functional analyses. Our protocol allows high editing efficiencies and unimpaired cell viability and differentiation, with scalability, suitability for functional assessment of editing outcomes and high flexibility in the application to different editors.